Social and Demographic Determinants of Online Disinformation - Stefania E. Stoica (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This study aims to explore the social and demographic determinants of narrative influence in Romania, with a specific focus on how disinformation campaigns are tailored to different age groups based on their digital behavior. By examining the intersection of social media consumption habits, cultural biases, and socio-economic factors, this paper seeks to contribute to the growing body of literature on developing more effective strategies to combat the spread of disinformation and protect the integrity of societal resilience in Romania’s digital landscape.